2019
DOI: 10.1128/jb.00270-19
|View full text |Cite
|
Sign up to set email alerts
|

Chitin Heterodisaccharide, Released from Chitin by Chitinase and Chitin Oligosaccharide Deacetylase, Enhances the Chitin-Metabolizing Ability of Vibrio parahaemolyticus

Abstract: Vibrio parahaemolyticus RIMD2210633 secretes both chitinase and chitin oligosaccharide deacetylase and produces β-N-acetyl-d-glucosaminyl-(1,4)-d-glucosamine (GlcNAc-GlcN) from chitin. Previously, we reported that GlcNAc-GlcN induces chitinase production by several strains of Vibrio harboring chitin oligosaccharide deacetylase genes (T. Hirano, K. Kadokura, T. Ikegami, Y. Shigeta, et al., Glycobiology 19:1046–1053, 2009). The metabolism of chitin by Vibrio was speculated on the basis of the findings of previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Since VPA1177 has been shown to be transcribed [75] and to produce a translated protein in V. parahaemolyticus [35], we sought to determine whether the product of chiA-3 from V.…”
Section: Identification and Characterisation Of Chia-3mentioning
confidence: 99%
See 3 more Smart Citations
“…Since VPA1177 has been shown to be transcribed [75] and to produce a translated protein in V. parahaemolyticus [35], we sought to determine whether the product of chiA-3 from V.…”
Section: Identification and Characterisation Of Chia-3mentioning
confidence: 99%
“…The pathways by which chitin is degraded and utilised by V. cholerae have been described in detail [30], as it has been in other members of the genus (e.g., [31][32][33][34][35][36][37][38]). Although a comprehensive review of the chitin utilisation pathway is beyond the scope of this manuscript, it is important to appreciate the complexity of this pathway.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chitinase, on the other hand, generally plays an important role in the degradation of the crustacean rich biopolymer chitin, converting it into nutrients for marine bacteria (Frederiksen et al, 2013). It is of course not present in all V. parahaemolyticus strains (Hirano et al, 2019). However, the absence of chitinase in AHPND V. parahaemolyticus XN9 indicated that chitinase might not be essential in shrimp pathogenesis or induced in vitro.…”
Section: Parahaemolyticusmentioning
confidence: 99%